Considerations of CD8+ T Cells for Optimized Vaccine Strategies Against Respiratory Viruses - Hirai, Toshiro; Yoshioka, Yasuo (Frontiers in Immunology, 2022)
The primary goal of vaccines that protect against respiratory viruses appears to be the induction of neutralizing antibodies for a long period. Although this goal need not be changed, recent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants have drawn strong attention to another arm of acquired immunity, CD8+ T cells, which are also called killer T cells. Recent evidence accumulated during the coronavirus disease 2019 (COVID-19) pandemic has revealed that even variants of SARS-CoV-2 that escaped from neutralizing-antibodies that were induced by either infection or vaccination could not escape from CD8+ T cell-mediated immunity. In addition, although traditional vaccine platforms, such as inactivated virus and subunit vaccines, are less efficient in inducing CD8+ T cells, newly introduced platforms for SARS-CoV-2, namely, mRNA and adenoviral vector vaccines, can induce strong CD8+ T cell-mediated immunity in addition to inducing neutralizing antibodies. However, CD8+ T cells function locally and need to be at the site of infection to control it. To fully utilize the protective performance of CD8+ T cells, it would be insufficient to induce only memory cells circulating in blood, using injectable vaccines; mucosal immunization could be required to set up CD8+ T cells for the optimal protection. CD8+ T cells might also contribute to the pathology of the infection, change their function with age and respond differently to booster vaccines in comparison with antibodies. Herein, we overview cutting-edge ideas on CD8+ T cell-mediated immunity that can enable the rational design of vaccines for respiratory viruses.